Knowledge, awareness and perception about equine glanders among veterinarians and medical professionals in India - Raj, Ana; Pathak, Anubha; Karuppusamy, Shanmugasundaram; Tripathi, Bhupendra Nath; Tripathi, Hema; Singha, Harisankar (Frontiers in Veterinary Science, 2024)
Glanders is a highly infectious and notifiable disease of equines that occurs due to Burkholderia mallei. In India, glanders re-emerged in 2006 and thereafter regular outbreaks have been reported in various states (n=14). Frequent and prolonged contact with equids with glanders may transmit B. mallei infection to humans. This study was designed to learn more about the Knowledge, Awareness and Perception (KAP) of veterinarians, para veterinarians, and physicians about equine glanders, which will help in enhancing the nation-wide glanders eradication programme. A total of 165 respondent's from11 Indian states and one union territory were surveyed. Most of the respondents (n=160) were from equine glanders affected or endemic states. Knowledge gap analysis revealed that 40.3% and 22% of the participants were not aware of government regulations and the transmission of glanders, respectively. These are major concerns given the wide spread occurrence of disease in the country. Awareness test on glanders revealed that 65(39.4%) participants would collect biological samples for laboratory confirmation, 67(40.6%) would inform the concerned authorities and106 (64.2%) replied that they would eliminate the glanders infected equines. Analysis of perception towards equine glanders showed that majority of the participants (n=113, 68.4%) observed that equine keepers were reluctant to disclose the clinical symptoms of B. mallei infection. Furthermore, non-co-operation and unwillingness by superiors (33.9%), financial (31%), administrative (28.4%), and technical limitations (27.8%) were major constraints under the perception analysis. This study reveals that veterinarians need to be educated on governmental policies and guidelines on equine glanders with regular training and awareness programs. Intersectoral co-ordination to investigate human glanders is also needed.